2022
DOI: 10.1021/acs.jchemed.2c00267
|View full text |Cite
|
Sign up to set email alerts
|

Goals for the Undergraduate Instructional Inorganic Chemistry Laboratory When Course-Based Undergraduate Research Experiences Are Implemented: A National Survey

Abstract: Course-based undergraduate research experiences (CUREs) are a promising approach for incorporating inquiry-based instruction into the undergraduate chemistry laboratory curriculum. This study used data from a national survey of inorganic chemistry faculty members (n = 142) to investigate CURE implementation in the inorganic chemistry instructional laboratory. Results indicate that faculty members who implement CUREs place greater emphasis on a distinct set of instructional goals when compared to faculty member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The articles on faculty perspectives include a national survey of inorganic chemistry faculty members and a survey of instructors implementing the BASIL CURE across several institutions . The national survey identified that the use of CUREs is limited (though a majority of faculty indicate the likelihood of implementing a CURE in the future), and that instructors who implement CUREs report distinct instructional goals aligned with CURE pedagogy . Both articles detail perspectives on the logistical aspects of implementing CUREs, such as institutional and departmental factors that affect CURE implementation (including available funding, resources, and teaching assistant support). , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles on faculty perspectives include a national survey of inorganic chemistry faculty members and a survey of instructors implementing the BASIL CURE across several institutions . The national survey identified that the use of CUREs is limited (though a majority of faculty indicate the likelihood of implementing a CURE in the future), and that instructors who implement CUREs report distinct instructional goals aligned with CURE pedagogy . Both articles detail perspectives on the logistical aspects of implementing CUREs, such as institutional and departmental factors that affect CURE implementation (including available funding, resources, and teaching assistant support). , …”
Section: Resultsmentioning
confidence: 99%
“…79,90,106 The remaining research articles provided contributions toward assessing student outcomes from participating in CUREs (2 articles, or 17%) 107,108 or detailed faculty perspectives of CUREs (2 articles, or 17%). 109,110 In the research focused on assessing student outcomes from CURE participation, one article presents a procedure for developing course-specific anticipated learning outcomes in order to guide assessment design. 107 The other article reports instruments for evaluating students' written reflections or poster session interview responses to assess learning outcomes for CUREs; the researchers used the instruments to identify strengths and weaknesses of undergraduates with differing amounts of research experience on skills such as integrating evidence, explaining societal relevance, and critiquing experimental design.…”
Section: Trends In Research On Chemistry Curesmentioning
confidence: 99%
“…To further account for the nested nature of our data, departmental demographic variables found to be associated with chemistry faculty members' use of certain evidence-based pedagogies (e.g., ACS approval to award certified bachelor's degrees; see Table 8) are also included in the model. 8 Predictor variables for EBIP Tryout − Overall and EBIP Adoption − Overall analyses include all variables from EBIP Tryout − DCaT and EBIP Adoption − DCaT models, as well as 17 additional malleable factors widely reported in STEM education literature as being related to EBIP adoption (see Table 8). 29 These 17 malleable factors were originally included in multilevel modeling of EBIP adoption by Yik et al, 29 along with a literature overview of their influence on EBIP adoption and corresponding rationales for their inclusion as predictor variables.…”
Section: Multilevel Modelingmentioning
confidence: 99%
“…6,7 Given these benefits, a subset of chemistry educators are committed to implementing EBIPs in their undergraduate-level courses. 8 This commitment is reflected in the discipline's growing number of studentcentered curricular innovations, 9−11 chemistry education research studies investigating the use of EBIPs, 8,12−14 and special issues from the Journal of Chemical Education focused on student-centered pedagogies (e.g., ref 15). However, lecture-based approaches remain the predominant mode of instruction in undergraduate chemistry classrooms, including other STEM disciplines.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation